Killing the bill: The interplay of social comparisons and financial information on preferences for electricity-saving behaviors - Fabien Giauque; Mehdi Farsi; Sylvain Weber; Michael Puntiroli (University of Neuchâtel, Institute of Economic Research (IRENE), 2025)
Using a discrete choice experiment (DCE), we analyze how social comparisons and financial information influence households' preferences and trade-offs among three sustainable electricity demand behaviors: conservation actions, efficiency investments, and purchasing a green power mix. Our results show that while a strong majority favors sustainable behaviors over inaction, both interventions significantly increase the likelihood of choosing inaction. Heterogeneity analyses reveal that this negative effect is driven by households with above-average consumption. Furthermore, our findings highlight conflicting motivational mechanisms, suggesting that financial information within normative messages may crowd out intrinsic motivation
Keywords: D12; D91; Q48; 330; Electricity-saving behaviors; households' preferences; social comparisons; financial information; discrete choice experiment; mixed logit (MXL) model; crowding out effect